The rich get richer and the poor get poorer - the Matthew mechanism as an approach to explain selection effects and the occurrence of multiple medalists in the "production" of international success in alpine ski racing - Michael Barth; Arne Güllich; Eike Emrich (Bern Open Publishing, 2018)
The study addresses two questions that are under debate in the literature and exemplifies their examination in alpine ski racing. Firstly, are successful athletes the product of a long-term continuous intervention and/or socialization process or do they rather emerge via repeated selection processes? Secondly, to which extent is a nations' collective success composed of many athletes' singular successes or of a few athletes' multiple successes? The study involved the national squad of the Austrian Ski Federation. Data collection comprised membership in a national squad and World or Olympic medal success and was carried out via document analysis (seasons: 1986-2016). The mean annual athlete turnover rate ranged from 24-57% across squad levels while the turnover rate varied substantially over time within each squad level. Among all national squad athletes, the incidence of being a successful (i.e., medal winning) National Team athlete was 8.9% (95% CI: 6.0%; 12.5%). Twenty-eight athletes won a total of 112 medals, 21 athletes achieved winning two or more medals. The six most successful athletes won 56 medals, comprising 50% of all medals won. The study suggests that successful elite athletes emerge from repeated selection and filtering processes. The observation of multiple medalists and a high concentration of exceptional success among a few athletes is reflected with regard to potential causes that rest on characteristics of the individual athlete, on social mechanisms (e.g., Matthew mechanism) of the elite sports system, or both.